Truth, Silence, and Violence in Emerging States 2018
DOI: 10.4324/9781351141123-4
|View full text |Cite
|
Sign up to set email alerts
|

Euphemism, censorship, and the vocabularies of silence in Burundi

Abstract: Burundi's postcolonial history is often recounted through the dates of great événements, the "events", isolated flashes of political violence that seem to trace out a sequential chain across the decades

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Aidan Russell documents the co-production of publicly non-contestable truths about violence in Burundi, denials and silences: 'A truth [about horrible events would be] turned to foment opacity around the crimes of the state ' (2018: 66, 2019). Even if euphemism and ambiguous descriptions of violence enabled multiple interpretations of past violence, succeeding authoritarian regimes imposed one political truth and many silences (Russell 2018). In both case studies, we observe the materiality of exhumed remains strengthens the political power of discursive claims to truth.…”
Section: Conclusion: the Management Of Mass Graves After Confl Ict An...mentioning
confidence: 71%
See 2 more Smart Citations
“…Aidan Russell documents the co-production of publicly non-contestable truths about violence in Burundi, denials and silences: 'A truth [about horrible events would be] turned to foment opacity around the crimes of the state ' (2018: 66, 2019). Even if euphemism and ambiguous descriptions of violence enabled multiple interpretations of past violence, succeeding authoritarian regimes imposed one political truth and many silences (Russell 2018). In both case studies, we observe the materiality of exhumed remains strengthens the political power of discursive claims to truth.…”
Section: Conclusion: the Management Of Mass Graves After Confl Ict An...mentioning
confidence: 71%
“…Under the fi rst mandate of the TRC (2014-2018), there were eff orts to document a wide diversity of events that aff ected diff erent constituencies across various periods and parts of the country; these eff orts have been abandoned with an increasing focus on 1972. Despite recurrent claims to truth, the TRC and exhumation practices are reproducing older patterns of implicit truths, imposed silenced and denial (Russell 2018), with strong political implications.…”
Section: Scaling Up Mass Graves Exhumations Through the Trcmentioning
confidence: 98%
See 1 more Smart Citation
“…Meanwhile, anthropologists have shown that violence can be dealt with in many ways in diff erent contexts. It is, for instance, well-known in the African Great Lakes region that silence is a socially constructed and morally accepted way of dealing with large scale violence (Ingelaere 2009;Russell 2019). Argenti and Schramm suggest that "we ought perhaps to pay still more attention to a politics of memory, or in other words to processes of appropriation, confl icting interests and overlapping discourses" (2010: 18, emphasis in original).…”
Section: Knowing Violencementioning
confidence: 99%